2021
DOI: 10.3389/fmolb.2021.598427
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Matrix-Based Signature Associated With Immune Microenvironment Predicts the Prognosis and Therapeutic Responses of Patients With Oesophageal Squamous Cell Carcinoma

Abstract: Evidence has suggested that the cancer-associated extracellular matrix (ECM) could be recognised as immune-related biomarkers that modulate tumour progression and expansion. However, the ECM-associated immune effect on esophageal squamous cell carcinoma (ESCC) prognosis and therapy has not been well characterised. In our study, we first constructed an ECM-related signature including four genes CST1, NELL2, ADAMTSL4, and ANGPTL7 by multivariate Cox regression analyses. This signature could serve as a marker to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Accumulating evidence has suggested that the ECM is associated with tumor aggression, metastasis, treatment sensitivity, and prognosis (Deligne and Midwood, 2021). The ECM was also reported to not only provide a physical barrier, preventing interaction between immune effectors or drugs and tumor cells, but can also modulate immune cell proliferation, differentiation, motility, and activation (Zhang et al, 2021). However, the role of the ECM signature in HCC classification has not been estimated, although a dynamic ECM was associated with HCC carcinogenesis, progression, and prognosis (Jeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that the ECM is associated with tumor aggression, metastasis, treatment sensitivity, and prognosis (Deligne and Midwood, 2021). The ECM was also reported to not only provide a physical barrier, preventing interaction between immune effectors or drugs and tumor cells, but can also modulate immune cell proliferation, differentiation, motility, and activation (Zhang et al, 2021). However, the role of the ECM signature in HCC classification has not been estimated, although a dynamic ECM was associated with HCC carcinogenesis, progression, and prognosis (Jeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic role of the riskscore was confirmed in the validation set, the related results of validation set being similar to those of the training set ( Figure 5D,5F ). Prior study has revealed a signature based on extracellular matrix (ECM) which could also be used to predict the OS of patients with ESCC ( 64 ). Micro(mi)RNAs are non-coding RNAs and are significantly associated with malignant initiation and progression ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 ] showed ADAMTSL4 to be directly linked to poor prognosis in patients with Glioblastoma Multiforme and the expression of ADAMTSL4 to be correlated with immune responses such as infiltration of the tumour by immune cells. Deregulation of ADAMTSL4 has also been reported in nasopharyngeal carcinoma [ 51 ], acute lymphoblastic leukaemia [ 52 ] and oesophageal squamous cell carcinoma [ 53 ]. Low expression of ADAMTS15 was demonstrated to be associated with poor prognosis in breast carcinoma [ 54 ].…”
Section: Discussionmentioning
confidence: 99%